What makes us apes? The emotional building blocks of intersubjectivity in hominids. Issue 3 (4th May 2022) - Demuru, Elisa; Clay, Zanna; Norscia, Ivan
Highlights: Intersubjectivity has often been lauded as one of the defining features that separates humans and other extant hominids. Intersubjectivity and empathy are different, yet related, phenomena. The study of emotions and empathy-related abilities can provide insights into the ontogeny and evolution of intersubjectivity. Intersubjectivity, which refers to the capacity to create shared value or connection between individuals, is a complex and multi-faceted phenomenon involving both cognitive and affective components. Intersubjectivity has often been lauded as one of the defining features that separates the social minds and existence of humans and non-human animals. Despite the apparently profound importance of inter-subjectivity for the socio-cognitive functioning of our species, we know surprisingly little about its evolution, nor how its evolution relates to the evolution of other related phenomena, such as empathy. In this review, we embrace the "bottom-up" perspective to consider recent theoretical and empirical advances in the fields of non-human animal cognition and emotion and what they can tell us about how complex socio-emotional capacities evolve. In particular, we focus on great ape species. Given their close phylogenetic relationship to us, great apes (the non-human, extant hominids) offer a unique lens to identify which of our capacities may be evolutionarily derived or phylogenetically shared.